Uganda : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2009)
This Selected Issues paper on Uganda discusses the progress toward harmonization of capital account regulations and capital market integration. A unified East African Community financial market would offer several benefits to the regional economy. It would expand the opportunities for savings and investment financing, encourage more competition among banks and financial institutions, and lower transaction costs through economies of scale. Greater diversification, risk management, and consumption smoothing would also be possible in a broader financial market, while monetary union would eliminate exchange rate risk within the region.